Psychometric evidence of a brief measure of resilience in non-institutionalized Peruvian older adults - Caycho Rodríguez, Tomás (2018)
Resilience is understood as the domain of personal resources and contextual factors that allow for a successful coping and enhance positive adaptation to the different stressors during the lifespan, thereby being important for a healthy and successful aging. Nowadays, several brief instruments have been developed to measure resilience, such as the Brief Resilient Coping Scale (BRCS), an instrument that measures the ability of people to confront stress in an adaptive way. In this vein, the study provides evidence of the validity and reliability of the BRCS in non-institutionalized older adults in Peru. Two hundred thirty-six elderly people of both genders, 78.4% women and 21.6% men, with a mean age of 72.8 years (SD= 6.90), who answered the Spanish version of the BRCS and other scales to measure satisfaction with life, humor as coping, and depression. Confirmatory factor analysis corroborates the one-dimensional structure of the BRCS. The coefficients of internal consistency, Chronbach's alpha and omega, indicated an adequate reliability of the BRCS. Both the adjustment indices of the model and the values of the coefficients of reliability were higher compared to those reported in the literature. The BRCS showed positive and significant correlations with satisfaction with life and humor as coping (p < .01). Likewise, negative and significant correlations were observed with depression (p < .01). The results show that the BRCS has proved valid and reliable, supporting its use as a short measure of resilience in older Peruvians.